Vitamins A, C, and E and ?-carotene content in seeds of seven species of Vicia L. - Sahin, A; Kiran, Y; Karatas, F; Sonmez, S (Blackwell Publishing Asia, 2005)
To determine the vitamins A, C, and E and P-carotene content of Vicia species that can be used in animal feed, a high performance liquid chromatography (HPLC) method was used to investigate the vitamin and P-carotene content in mature and immature seeds of seven Vicia species (Vicia anatolica Turrill., V ervilia (L.) Willd., V michauxii Sprengel, V mollis Boiss. et Hausskn. ex Boiss., V noeana Reuter ex Boiss., V. peregrina L., and V. sericocarpa Fenzl.), which are useful plants in animal feed in the eastern Anatolia region in Turkey. The vitamin content was found to differ between mature and immature seeds. The levels of vitamins A, C, and E and P-carotene were higher in mature seeds than in immature seeds (P < 0.01).
Keywords: high performance liquid chromatography (HPLC); seed; Vicia; vitamin